Stability analysis of low-voltage direct current system with time-varying delay - Ning Liu; Wei Qian (Systems Science & Control Engineering, 2024)
This paper investigates the stability analysis of LVDC systems with time-varying delay. A hierarchical control model is constructed for LVDC systems subjected to time-varying delay. Furthermore, a novel Lyapunov-Krasovskii functional is developed by introducing the augmented terms and the delay-dependent matrices. To reduce the conservativeness of stability criteria, the constructed functional is effectively estimated by using the quadratic function inequalities and composite relaxation integral inequalities. Finally, the simulation results are given to validate the proposed method with a higher time-delay stability margin of LVDC systems.